2015
DOI: 10.1007/s00125-015-3667-8
|View full text |Cite
|
Sign up to set email alerts
|

p66Shc deletion or deficiency protects from obesity but not metabolic dysfunction in mice and humans

Abstract: In mice and humans, reduced p66Shc levels protect from obesity, but not from ectopic fat accumulation, glucose intolerance and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
1
31
1
Order By: Relevance
“…It has been demonstrated that p66shc −/− mice are protected from HFD-induced obesity 14, 15 . Similarly, protection by p66shc deletion was observed in lep Ob/Ob mice 20 , although the beneficial effects on glucose intolerance and insulin resistance have been questioned 21 . Muscle atrophy and weakness have been linked to obesity 31, 32 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that p66shc −/− mice are protected from HFD-induced obesity 14, 15 . Similarly, protection by p66shc deletion was observed in lep Ob/Ob mice 20 , although the beneficial effects on glucose intolerance and insulin resistance have been questioned 21 . Muscle atrophy and weakness have been linked to obesity 31, 32 .…”
Section: Resultsmentioning
confidence: 99%
“…Comparison with a “pure” p66shc −/− mouse strain suggested that, while p66shc deletion accounts for the increased insulin sensitivity and glucose tolerance, resistance to diet-induced obesity may be due to p46shc overexpression in adipose tissue 15 . Protection from obesity was reported also in p66shc −/− lep Ob/Ob mice, a genetic model of obesity 20 , even though adipose tissue analysis and metabolic parameters demonstrated that p66shc deletion does not protect lep Ob/Ob mice from glucose intolerance and insulin resistance 21 , suggesting a different role of p66shc in different obesity models.…”
Section: Introductionmentioning
confidence: 95%
“…However, a role for p66Shc in MetS is still debated. Ciciliot et al (178) have recently shown that p66Shc-KO mice, following an HFD regimen, were leaner than their wild-type counterparts but equally glucose intolerant and insulin resistant. In addition, patients with reduced p66Shc levels were less obese, but were not protected from other features of MetS features-diabetes, dyslipidemia, and hypertension (178).…”
Section: P66shc: a Healthspan Gene Involved In Oxidative Stress Fat mentioning
confidence: 99%
“…Interestingly, deletion of p66Shc by suppressing H 2 O 2 production inhibited insulin-dependent adipogenesis (12). As a result, p66Shc 2/2 mice were leaner than wild-type (WT) mice fed a standard diet (SD), fed a high-fat diet (HFD), or under leptin deficiency (Lep Ob/Ob ) (12)(13)(14)(15). While lower body weight of p66Shc 2/2 mice has been confirmed in several laboratories, the metabolic consequences of such a leaner phenotype are debated.…”
mentioning
confidence: 99%